Study on the performance of cement stabilized silty soil / Rabbiatul A’dawiyah Rosli - Rosli, Rabbiatul A’dawiyah (2006)
In Malaysia, silty soil deposit poses a difficult problem in civil engineering project. The low shear strength and high compressibility of silty soil have caused difficulties in excavation and construction of foundation. Chemical soil stabilization is an extensive method that has been used for improving the properties of soft soil. Cement is the most widely used additive for soil stabilization due to its high strength and availability. The primary objective of this study is to examine the effectiveness and performance of cement as a soil stabilization agent on fine soil (silty). This study will focus on the shear strength characteristic of silty soil treated with cement. Silty soil was taken from a site at Jalan Sungai Biawak, Permatang Pauh. The shear strength of the silty soil-cement was study in the laboratory. Other variable include in the study were cement content and curing period. The test result showed that the undrained shear strength of silty soil was improved with addition of cement. The plastic limit increase while liquid limit and plasticity index is decrease as increase the cement content. The optimum moisture content decrease and the maximum dry density is increase as increasing the percentage of cement. The Portland cement used as the stabilizing agent. The percentages of cement used in this study are 1%, 5% and 10% and curing for 1-day, 3-days, and 7-days. Curing day play an importance role in strength of treated soil, because strength increases with the age.